An evaluation on the impact of FDI, human capital formation, physical capital formation and foreign exchange rate fluctutations on the economic growth of Malaysia from 1970-2000 / Prof. Madya P.J. Atchiah, Karunagaran Madhavan and Deviga Vengedasalam - Atchiah, P.J.; Madhavan, Karunagaran; Vengedasalam, Deviga (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2005)
This paper investigates the impact of growth channels on Malaysian economy namely foreign direct investment (FDI), human capital formation (HCF), gross fixed capital formation (GFCF), extent of technological transmission (ETT) and foreign exchange rate (FER) between 1970 through 2000. In our study we employed multiple regression analysis and mediator models, to understand the impact of GFCF, HCF, FER, FDI, ETT and EXPEDU on economic growth rate. This analysis has yielded some interesting results that warrant further research and exploration. Both methodologies used in our study indicate that GFCF, HCF and EXPEDU are of important in influencing economic growth rates of Malaysia. The Granger Causality Study indicates that, in almost all cases, GDP rates seem to have a profound impact on GFCF, HCF and EXPED. Based on this causality study, it is our view that any deceleration in GDP can adversely affect the level of GFCF, GGS and EXPEDU which we consider important in affecting the economic growth rates of Malaysia.